Constructing a Spectral Down Converter to Enhance Cu(In, Ga)Se2 Solar Cell Performance Using Yttrium Aluminum Garnet:Ce3+ Ceramics. Issue 5 (3rd March 2020) - Xiong, Zhiyu; Gong, Junbo; Xiong, Yuan; Lan, Yuchi; Yin, Min; Ding, Zejun; Zhang, Zengming; Xiao, Xudong
Abstract : Spectral conversion has been widely applied in the field of luminescence and is potentially beneficial for photovoltaic solar cells. However, more was said than done for the down‐conversion effect in the past, and quite a number of existing reports overclaimed the observed performance enhancement from down conversion either by wrongly identifying the contributions or by unfairly comparing with an inappropriate reference. Herein, Ce‐doped Y3 Al5 O12 ceramics with suitable absorption and photoluminescence properties are chosen as the down‐conversion material for Cu(In, Ga)Se2 (CIGS) solar cells. By properly designing optical structures to integrate the down‐conversion material with the CIGS solar cell, the fluorescent photons are efficiently guided to the CIGS absorber layer in addition to eliminating the scattering and maintaining the antireflection (AR) for incident light. The Y3 Al5 O12 :Ce 3+ ceramic down converter on CIGS solar cells can bring an enhancement of 0.53 mA cm −2 to the short‐circuit current density solely from down conversion, which is responsible for the major increase in conversion efficiency from 18.5% to 19.0%. A positive down‐conversion effect is demonstrated over AR layer‐coated CIGS solar cells without misclaiming contributions from other accompanied effects or jeopardizing any other accompanying effects. Abstract : Yttrium aluminum garnet (YAG):Ce 3+ ceramic is chosen as the down converter for Cu(In, Ga)Se2 (CIGS) solar cells. With proper optical design, a 0.53 mA cm −2 increase in J sc solely from the down‐conversion effect is obtained, contributing to the majority of the overall efficiency enhancement from 18.5% to 19.0%.